Swing for Jython - Gibson, Robert (Springer, 2015)
This book shows you how to use Swing to add a GUI to your Jython scripts, with an emphasis on the WebSphere Application Server wsadmin utility. In fact, we're going to teach you Swing using Jython, and we're going to do it in a way that, hopefully, that makes your scripts easier for people to use, more robust, more understandable, and therefore easier to maintain.